Optimizing The Role Of Digitalization, Human Resource Practices, And Product Innovation As Mediation In Efforts To Build Resilience In Culinary Umkm In Garut District - Muharam, Husni; Rismanto, Hilman; Deri Alan Kurniawan; Rosita, Iis; Febianti, Adiesty Nur (Indonesian Scientific Publication, 2025)
Changes in the current digital era occur very quickly and lead to conditions that continue to change dynamically, so overcoming the increasing uncertainty in the organization becomes important and urgent, and the organization's ability to develop resilience is also essential. MSMEs face various challenges in the digital era, such as changes in consumer behavior, global competition, and economic uncertainty. The resilience of MSMEs is the primary determinant in overcoming these uncertainties. Understanding how digitalization and HR can complement each other creates excellence and product innovation. This study aims to determine how digitalization, human resources practices, and product innovation affect resilience (Study on Culinary MSMEs in Garut Regency). The research method used is quantitative with a descriptive approach. Primary data was obtained by distributing questionnaires to 100 respondents using probability and random sampling. The data analysis technique used in this study used PLS-SEM. The analysis results show that digitalization does not directly affect resilience; it directly affects resilience by being mediated by product innovation variables.